1984
DOI: 10.1007/bf00679984
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of atrial natriuretic factor in the heart and salivary glands

Abstract: Antibodies produced in the mouse by repeated intraperitoneal injections of partly purified atrial natriuretic factor (low molecular weight peptide (LMWP) and high molecular weight peptide (HMWP)) have been used to localize these factors by immunohistochemistry (immunofluorescence and immunoperoxidase method) and by immunocytochemistry (protein A-gold technique) in the heart of rats and of a variety of animal species including man and in the rat salivary glands. Immunofluorescence and the immunoperoxidase metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(61 citation statements)
references
References 27 publications
3
57
0
1
Order By: Relevance
“…The ANP presence in the ducts was probably related to the natriuretic activity of ANP, since saliva is an ion-rich fluid which content becomes modified during passage along the ductal epithelium in both intra-and extralobular ducts, where most of the NaCl is being reabsorbed [31]. Furthermore ANP in human parotid gland has the same localization as in rat [8,10] and rabbit [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANP presence in the ducts was probably related to the natriuretic activity of ANP, since saliva is an ion-rich fluid which content becomes modified during passage along the ductal epithelium in both intra-and extralobular ducts, where most of the NaCl is being reabsorbed [31]. Furthermore ANP in human parotid gland has the same localization as in rat [8,10] and rabbit [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cantin et al [8] found that in rat parotid gland ANP immunoreactivity was intense exclusively in the acinar cells; in sublingual gland only the serous cells were immunoreactive, whereas in submaxillary gland the reaction was weaker and distributed randomly in the gland. By contrast, Gutkowska and Nemer [9] found the ANF-immunoreactivity confined to the granular convoluted tubular cells of the submaxillary gland.…”
Section: Introductionmentioning
confidence: 97%
“…Recent use of the protein A-gold immunocytochemical technique has made apparent the atrial natriuretic polypeptide (ANP), which possesses potent diuretic, natriuretic and vasorelaxant activities and is localized in the specific atrial granules (DE BOLD et al, 1981;CANTIN et al, 1984). The granularity of the atrial cells has been known to alter in some experimentally induced water-electrolyte imbalances (MARTINEZ-P. and BENCOSME, 1966;CANTIN and HUET, 1973;DE BOLD, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have used immunohistochemical techniques to study the distribution of ANP and ANP-related peptides (cardiodilatin, atrial natriuretic factors, atriopeptin II) in mammalian hearts [2,4,7,8,10]. They have described that the most intensely granulated cardiocytes are located in the auricle and that the number of densely granulated cells is greater in the right atrium than in the left.…”
mentioning
confidence: 99%